Data Warehousing and Knowledge Discovery 7th International Conference, DaWak 2005, Copenhagen, Denmark, August 22-26, 2005, Proceedings - Tjoa, A Min.; Tjoa, A Min. (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2005)
For more than a decade, data warehousing and knowledge discovery technologies have been developing into key technologies for decision-making processes in com- nies. Since 1999, due to the relevant role of these technologies in academia and ind- try, the Data Warehousing and Knowledge Discovery (DaWaK) conference series have become an international forum where both practitioners and researchers share their findings, publish their relevant results and dispute in depth research issues and experiences on data warehousing and knowledge discovery systems and applications. The 7th International Conference on Data Warehousing and Knowledge Discovery (DaWaK 2005) continued series of successful conferences dedicated to these topics. In this edition, the conference tried to provide the right, logical balance between data warehousing and knowledge discovery. Regarding data warehousing, papers cover different relevant and still unsolved research problems, such as the modelling of ETL processes and integration problems, designing OLAP technologies from XML do- ments, modelling data warehouses and data mining applications together, impro- ments in query processing, partitioning and implementations. With regard to data mining, a variety of papers were presented on subjects including data mining te- niques, clustering, classification, text documents and classification, and patterns. These proceedings contain the technical papers that were selected for presentation at the conference. We received 196 abstracts, and finally received 162 papers from 38 countries, and the Program Committee eventually selected 51 papers, making an acceptance rate of 31.4 % of submitted papers.